Microphone republic: propaganda and indoctrination in guided democracy Indonesia - Sahul Hamid Mohamed Maiddin (N/A, 2015)
Microphone republic: propaganda and indoctrination in guided democracy Indonesia by Sahul Hamid Mohamed Maiddin